ANALYSIS AND CONTROL DESIGN OF PARALLEL PWM DC/DC BUCK CONVERTER - Alsheraidah, Asaad S.; Alsheraidah, Sabah S. (Iraqi Journal for Electrical and Electronic Engineering, 2006)
This paper presents a proposed configuration of paralleling scheme PWM DC/DC buck converter. The topological structure and operation principles are presented. A Bode plot diagram technique is used to study the stability of the scheme for different values of controller parameters and with a number of parallel modules. It is found that the results are confidence, and the proposed scheme can be used in high power applications by increasing the number of parallel modules.